Ciprofol in Children Undergoing Adenoidectomy and Adenotonsillectomy: A Retrospective Cohort Study - Zeng C; Li L; Wang M; Xiong J; Pang W; Yu H; He J; Wang X; Chen Y; Sun Y (Dove Medical Press, 2024)
Chao Zeng,1,* Lu Li,1,* Mengrui Wang,2,* Jun Xiong,1 Wenjuan Pang,1 Haiyan Yu,1 Jiadi He,1 Xuguang Wang,1 Yingying Chen,1 Yanyan Sun1 1Department of Anesthesiology, Shenzhen University General Hospital, Shenzhen University, Shenzhen, Guangdong, People's Republic of China; 2Department of Anesthesiology, Peking University Third Hospital, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Yanyan Sun; Jun Xiong, Department of Anesthesiology, Shenzhen University General Hospital, Shenzhen University, Shenzhen, Guangdong, People's Republic of China, Email b2008194@126.com; xiongjun107@hotmail.comObjective: Ciprofol is a novel anesthetic agent, its efficacy and safety had been verified and its clinical implementation has been expanded. However, the knowledge about ciprofol in children is meager. The aim of study is to evaluate the safety and effectiveness of ciprofol in general anesthesia in children undergoing adenoidectomy and adenotonsillectomy, compared with propofol.Materials: We retrospectively analyzed data of children who underwent adenoidectomy or adenotonsillectomy with general anesthesia from June to August 2023 to evaluate the safety and effectiveness of ciprofol. The primary outcomes included hemodynamic changes during induction and postoperative complications in post-anesthesia care unit. The secondary outcomes were extubation time, pediatric anesthesia emergence delirium (PAED) score. Meanwhile, subgroup analysis was performed based on age.Results: 301 children met the inclusion criteria, 157 received ciprofol induction and 144 received propofol. Patient demographics and operation-related information were similar in the two groups. However, the dosage of dexmedetomidine in the propofol group was significantly higher than that of the ciprofol group (p=0.001). The trends of hemodynamic shift during induction and intubation were the same in the two groups. The PAED scores on post-extubation 10min and 20min were significantly reduced in the ciprofol group (p< 0.001 and p=0.046). Moreover, in the ≤ 72 months and the > 72 months subgroups, the scores were also significantly lower in the ciprofol group on post-extubation 10min. With the score of > 10, the incidence of emergence delirium of the ciprofol group was significantly lower on post-extubation 10min and 20min in the population and the ≤ 72 months subgroups (p=0.03 and p=0.02). There were no obvious postoperative complications in both groups.Conclusion: Ciprofol exhibited advantageous characteristics in the induction of children, such as stable hemodynamics, a relatively lower incidence of postoperative delirium without apparent post-anesthesia complications. Ciprofol may emerge as a novel option for general anesthesia in pediatric patients.Keywords: ciprofol, propofol, adenoidectomy, child, general anesthesia, delirium